Establishing a Reference Interval for an Estimate of Peripheral Insulin Resistance in a Group of Iraqi People - Al-Naemi, Amjad (Open Access Macedonian Journal of Medical Sciences, 2022)
Background and aims: Insulin resistance (IR) is the cornerstone in pathophysiology of T2DM. Identifying people with IR can slow the progress to diabetes. Triglyceride and glucose index (TyG index) is a simple tool to assess IR without insulin measurement. This study aims at establishing the reference interval for TyG index in apparently healthy Iraqis. Material and method: This study involved (77) apparently healthy adults (41 men and 36 women) in Mosul, Iraq. Fasting Serum lipids, glucose and insulin were measured and BMI was calculated. The modified TyG index was calculated and compared to other surrogate measures of IR and its reference interval was calculated. Results: TyG index values were normally distributed and significantly correlated with HOMA-IR, Mc-Auley index, QUICKI, and triglycerides/ HDL-c index (r= 0.322, p= 0.004; r=-0.68, p<0001; r= -0.29, p=0.01; r=0.84, p<0.0001respectively). ANOVA and PostHoc Duncan’s analyses revealed significant differences in mean TyG between (lean people) and (overweight and obese subjects), (p=0.02). BMI- based TyG reference intervals were calculated as (4.11- 4.91) and (4.25- 5.05) respectively. This is the first study in Iraq to set a reference interval for TyG index. Values should be interpreted according to BMI.